Peter Pan - Barrie, J. M. (Italy. ELI - Young Reader, 2009)
The story of a boy who never grew up, with his friends Wendy and the jealous fairy Tinker Bell. Why are there no Lost Girls in Neverland? What did the crocodile want to eat?
Picture dictionary, games and activities.
Keywords: Adventure; Elementary level; Classroom activities; Story